Desenvolvimento de software orçamentário com base na linguagem visual basic - Nepomuceno, Arlean Fernandes (Universidade Federal Rural do Semi-Árido, 2018)
The budgeting stage is fundamental for the control of materials used in a work, as it is necessary to develop the materials used in the construction of an enterprise. Budgeting is a necessary tool for project planning and control. Aiming at this access problem, software was developed based on the basic visual programming language (VBA), in order to facilitate the use of software in the elaboration of its budgets. The methodology used was initially open to the observational method, in order to investigate other softwares for the development of budgets for civil construction, identifying opportunities for improvement. Consequently, it continued with a literature review on the requirements needed to prepare a budget, and how it programmed the functions with a language (VBA), which enabled the user to develop a budget with ease. For this we used Visual Basic Editor (VBE) objects such as listbox, frames, command button, checkbox, textbox and the like. Finally, with the software developed in accordance with its own budget application for the VBA language, and using as a database for a SINAPI table, as well as an accomplishment of registrations, research, edition and edition of suppliers, clients, inputs, services and own compositions.
Monografia
Keywords: Orçamento de obras; SINAPI; Excel; Access; VBA; Budget of works; SINAPI; Excel; Access; VBA; ENGENHARIAS::ENGENHARIA CIVIL